Amplification and Saturation of Turbulent Magnetic Fields in Collapsing Primordial Gas Clouds - Sho Higashi; Hajime Susa; Christoph Federrath; Gen Chiaki (The Astrophysical Journal, 2024)
Recent numerical studies suggest that magnetic fields play an important role in primordial star formation in the early Universe. However, the detailed evolution of the magnetic field in the collapse phase still has uncertainties because of the complicated physics associated with turbulence in a collapsing magnetized system. Here, we perform a suite of numerical MHD simulations that follow the collapse of magnetized, turbulent primordial gas clouds to investigate the evolution of the magnetic field associated with the turbulence, assuming a polytropic equation of state with exponent γ _eff and with various numerical resolutions. In addition, we generalize the analytic theory of magnetic field growth/saturation so that it can deal with various exponents γ _eff and turbulence energy spectra. We find that the numerical results are well reproduced by the theory for various γ _eff through the collapse phase during the formation of the first stars. The magnetic field is eventually amplified by a factor of 10 ^12 –10 ^15 due to kinematic and nonlinear turbulent dynamo effects and reaches 3%–100% of the equipartition level, depending on γ _eff . We also find that the transition between the kinematic and nonlinear stages can be analytically estimated. These results indicate that the strong magnetic field accompanied by supersonic turbulence is a general property and suggest that it can play a crucial role in the formation of the first stars.